PEMETAAN JALUR TRAYEK ANGKUTAN UMUM DAN FASILITAS SOSIAL BERBASIS WEBGIS DI KOTA BUKITTINGGI - Prabowo, Rizky; Yulfa, Arie (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
ABSTRACT In daily life in urban areas, especially in the city of Bukittinggi, identical with a lot of transportation because it is one of the community needs. With the existence of transportation, people can do more various daily activities for efficiently, especially in terms of time and energy. Therefore, a study has been made to determine the distribution of social facilities around the angkot route operating in Bukittinggi City. The method used is the R&D or Research and Development research method. R&D is a research method used to produce certain products and test the effectiveness of these products. The stages in this research use a waterfall development model. The results of this study indicate that there are 13 angkot majors in Bukittinggi City that pass through various existing social facilities, especially schools, offices, hospitals, and tourist attractions. The distribution of angkot routes in the city of Bukittinggi can be visualized and viewed at the domain address kelilingbukittinggi.gis.co.id to make it easier for the public to obtain information regarding the distribution of social facilities that are passed by the angkot routes.